Szanse i zagrożenia pracowników społeczeństwa informacyjnego - Miczyńska-Kowalska, Maria; Drozd, Izabela (MITEL, 2004)
Obecnie żyjemy w społeczeństwie informacyjnym. Wiedza jest podstawą pracy organizacji w społeczeństwie informacyjnym. Z jednej strony wiąże się to ze wzrostem znaczenia zasobów ludzkich i wzrostem roli pracy ludzkiej. Z drugiej strony, wiąże się to z ewolucją na rynku pracy. artykuł zawiera refleksje na temat problemów z pracą i przyszłości pracowników w perspektywie ewolucji teorii zarządzania.

Nowadays we live in information society. Knowledge is a base of organization`s working in information society. On the one hand, it implicates growth of human resources significance and rise of human work role. On the other hand, it implicates evoluation on the work market. The article includes reflections about the work problems and the future of workers in perspective of management`s theory evoluation.
Chances and Threats of Information Society Workers